The CALorimetric Electron Telescope (CALET) on the International Space Station: Results from the First Two Years On Orbit. (February 2019) - Asaoka, Y; Adriani, O; Akaike, Y; Asano, K; Bagliesi, M G; Berti, E; Bigongiari, G; Binns, W R; Bonechi, S; Bongi, M; Bruno, A; Brogi, P; et al.
Abstract: The CALorimetric Electron Telescope (CALET) is a high-energy astroparticle physics space experiment installed on the International Space Station (ISS), developed and operated by Japan in collaboration with Italy and the United States. The CALET mission goals include the investigation of possible nearby sources of high-energy electrons, of the details of galactic particle acceleration and propagation, and of potential signatures of dark matter. CALET measures the cosmic-ray electron+positron flux up to 20 TeV, gamma-rays up to 10 TeV, and nuclei with Z=1 to 40 up to 1, 000 TeV for the more abundant elements during a long-term observation aboard the ISS. Starting science operation in mid-October 2015, CALET performed continuous observation without major interruption with close to 20 million triggered events over 10 GeV per month. Based on the data taken during the first two-years, we present an overview of CALET observations: 1) Electron+positron energy spectrum, 2) Nuclei analysis, 3) Gamma-ray observation including a characterization of on-orbit performance. Results of the electromagnetic counterpart search for LIGO/Virgo gravitational wave events are discussed as well.